2014
DOI: 10.1016/j.molcel.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Dependent Regulation of Mitotic Protein Degradation

Abstract: Accurate cell division depends on tightly regulated ubiquitylation events catalyzed by the anaphase-promoting complex. Among its many substrates, the APC/C triggers the degradation of proteins that stabilize the mitotic spindle, and loss or accumulation of such spindle assembly factors can result in aneuploidy and cancer. Although critical for cell division, it has remained poorly understood how the timing of spindle assembly factor degradation is established during mitosis. Here, we report that active spindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Localization of substrates is also important. APC/C substrates that promote mitotic spindle assembly are concentrated on spindle microtubules and hence protected from degradation 80 . Thus substrates are post-translationally modified or differentially localized to regulate timing of their degradation in mitosis.…”
Section: The Apc/c Ubiquitylation Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Localization of substrates is also important. APC/C substrates that promote mitotic spindle assembly are concentrated on spindle microtubules and hence protected from degradation 80 . Thus substrates are post-translationally modified or differentially localized to regulate timing of their degradation in mitosis.…”
Section: The Apc/c Ubiquitylation Pathwaymentioning
confidence: 99%
“…In addition the presence of intact microtubules might sequester substrates or promote the transport of the APC/C to favorable subcellular locations (e.g. to chromosomes) for activation 80, 90 .…”
Section: Regulation Of the Apc/c In Early Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…Rape and colleagues [107,108 ] have discovered thatonce anaphase begins and the Anaphase Promoting Complex (APC/C) is activated by successful chromosome attachmenta higher level of regulation takes over. They found that, unlike cyclin B1 which is ubiquitinated and degraded at the very onset of anaphase, SAFs such as TPX2, HURP, and NuSAP, remain stable through anaphase.…”
Section: New Cellular Arenas For Karyopherin/rangtp Regulation Karyopmentioning
confidence: 99%